Comparing Wound Complication Rate Between Stappled Closure Vs Sutured Closure for Clean Abdominal Wounds - Asad, Sunya; Saeed, Bilal; Ilyas, Sohail; Shameem, Asad; Awan, Leena Hussain; Qureshi, Tansheet Mazhar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the wound complication rate between stappled closure vs sutured closure for clean abdominal wounds. Study Design: Quasi experimental study. Place and Duration of study: Department of General Surgery Combined Military Hospital Rawalpindi, Pakistan from Feb to July 24. Methodology: A total of 256 patients who fulfilled the selection criteria were enrolled in the study after taking written informed consent. The patients were divided into two groups i.e. 128 each by odd and even number. Patients in Group-A underwent stappled closure and in Group-B underwent suture closure of the abdominal wounds and the outcome measures were assessed till the patients were discharged. Findings were noted down and were subjected to statistical analysis. Results: A total of 256 patients were assessed and were randomized into two groups of equal number i.e. 128 in each group. The mean age of patients was 39.7±8.2 years in Group-A and 40.7±8.3 years in Group-B. SSI was seen in 10(7.8%) patients in Group-A and 23 (18%) patients in Group-B (p=0.015). Wound dehiscence was seen in 2(1.6%) patients in Group-A and 11(8.6%) patients in Group-B (p=0.010). Cosmetic appearance was reported good by 116(90.6%) patients in Group-A and 79(61.7%) patients in Group-B (p< 0.001). Conclusion: Stappled closure of clean abdominal wounds is significantly associated with lesser wound complication as compared to sutured closure.